ANALYSES OF WATER BALANCE AND ANNUAL, SEASONAL AND MONTHLY PLUVIOMETRIC VARIABILITY IN PIONEER NORTHERN PARANÁ STATE MESOREGION, BRAZIL - Caldana, Nathan Felipe da Silva; Ferreira, Luiz Gustavo Batista; da Silva, Iara; Aguiar e Silva, Marcelo Augusto (Revista Brasileira de Climatologia, 2020)
The rainfall variability has a key relevance on human activities. The frequency of extreme events, such as droughts and intense rains, results in severe impacts on crops, urban activities, water resources, health and the environment on a local or regional scale. The estimation of the frequency, impacts and severity of these events is essential for planning human activities. The purpose of this work was to analyze the rainfall variability and the water balance in the Northern Paraná state Mesoregion (PNPM) in the annual, seasonal and monthly time scales. For this, we used the annual, seasonal, monthly and daily time scales with the time from 1976 to 2018. For the better understanding, we used analysis using thematic maps with regionalization through interpolations and isohyets, box plot and dendogram. A large regional discrepancy in precipitation was identified in the analyzed mesoregion. In all the time scales analyzed in the region, there were alarming variations, which can bring perspectives for regional planning. We verified the Northwestern portion of the region, near to the municipality of Leópolis, had the lowest rainfall and the worst scenarios evaluated in the water balance, while the upper portion, in the Southwest, near Sapopema, presented more rain and less risk of drought. The average climatological water balance in the region showed a low deficit in the month of August, however when testing scenarios of dry years, the entire region showed water deficiency throughout the year.